Sosialisasi Mekanisme Kontrol Ultraviolet-C (UVC) Desinfektan Penanganan Covid -19 di Kabupaten Pinrang - Mochtar, Andi Amijoyo; Sule, Luther; Tarakka, Rustan; Azis, Nasruddin; Mire, Baharuddin; Mangkau, Andi; ., Fauzan (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
Public services are interactions between society and the government as public servants. This service activity involved the Pinrang Regency Investment and Integrated Service Agency (DPMPTS) and academics from the Mechanical Department, Faculty of Engineering, Hasanuddin University. Utilizing this disinfectant tool can help the DPMPTS service in terms of air sterilization and preventing the spread of Covid-19 in community service spaces. The problem that arises is the level of interaction between the community who needs services and DPMPTS employees as service providers who are quite vulnerable to the spread of viruses and bacteria. This can cause the spread of disease, so tools are needed that can reduce the impact of the spread of the disease. The use of Ultraviolet C (UVC) is a disinfectant tool that has been proven effective in killing microorganisms, one of which is the COVID-19 virus. The service method is carried out using an outreach mechanism at the DPMPTS agency which is attended by technical government agencies and several participating local communities. The process of implementing socialization uses a questionnaire mechanism consisting of pre-test and post-test. At the start of the socialization, the number of respondents who filled out the questionnaire was 18 people consisting of 8 government representatives and 10 community representatives or a total of 18 respondents. In the pre-test results, it was found that only 3 people understood the function of the mobile robot disinfectant system mechanism and 15 people did not understand. After the socialization was carried out, better results were obtained with 17 people who understood and 1 person who still did not understand the working system of the mobile disinfectant robot. Therefore, it is recommended to use mobile disinfectant robots in DPMPTS public service spaces to reduce the effects of spreading viruses and bacteria.